Training Bachelors for Practical Work with Elementary School Children Learning Difficulties in the course of Internship - Adaskina A.A; Sunnatova R.I (Moscow State University of Psychology and Education, 2019)
The article describes the experience of organizing internship for bachelor students pursuing studies on pedagogical psychology with specialization as elementary school teachers. Students' practical work was planned on the basis of the educational institution's specific objectives. It was included into the school psychological service current working plans of work with poorly performing pupils. The internship was held in the first semester of the senior year and consisted of several stages. At first, the students performed diagnostic assessment of children who, from teachers' perspective, had learning difficulties, using the diagnostic complex by L.A. Yasyukova. At the next stage, interns conducted remedial classes in small groups (2 students were attached to a group of 6-7 children). The remedial sessions were aimed at developing conception, logical and abstract thinking both on verbal and non-verbal material, and also included tasks on practicing intentional reading. The level of difficulty was initially selected in accordance with the diagnostics results, and then was being corrected on the basis of reporting forms the interns filled up after each class. The article summarizes the preliminary results of the described internship organizing technique and discusses its further prospects.